The historical experience of the people in Zeitun Tolgurov’s epic “The big dipper” - A. D. Atabieva; A. M. Sarbasheva (Кавказология)
In this research area, interest is an epic - scale canvas by the Balkarian prose writer Z. Tolgurova “Big Dipper”. According to all structural and content parameters (large format, panoramic view, aim reflection and comprehension of historical events, the length of the narrative in time and space, during battle scenes, parallel developing storylines, the conjugation of the destinies of the people and the main characters of the work) it is classified as an epic novel. Nationality is singled out as a defining feature. The purpose of the study is to identify the epic features of the novel and reflection degree in it of the historical experience of the people (the process of planting Soviet ideology, the tragic consequences of breaking the old patriarchal world, the denial of the former moral and ethical norms, the difficulties of coexistence of people in society, human adaptation to a spontaneously changing reality. The result of the dramatic events was not the achievement of universal equality or freedom of choice, but alienation and disunity in the ethnic environment, mutual hostility based on class. The reality of the period of the October Revolution is considered by Tolgurov in the evolution's context of individual consciousness. The study of the conceptual layers of the literary text made it possible to trace the transformation of the characters, to determine the spiritual and moral potential of each image, to determine the level of awareness and involvement of the characters in the historical process. The author’s evaluation line contributed to the realization of humanistic concepts and ideas. The work gradually reveals the ideological attitudes of representatives of different social strata, subjective ways of translating the mental component of the people (using the example of the ideological antipodes of the Nuh and the Cossack). All these provisions confirm the scale of the writer’s reflection of the specifics of the era, the relevance and artistic and aesthetic value of the novel.ts, the length of the narrative in time and space, the presence of battle scenes, parallel developing storylines, the conjugation of the destinies of the people and the main characters of the work) it is classified as an epic novel. Nationality is singled out as a defining feature. The purpose of the study is to identify the epic features of the novel and the degree of reflection in it of the historical experience of the people (the process of planting Soviet ideology, the tragic consequences of breaking the old patriarchal world, the denial of the former moral and ethical norms, the difficulties of coexistence of people in society, human adaptation to a spontaneously changing reality. The result of the dramatic events was not the achievement of universal equality or freedom of choice, but alienation and disunity in the ethnic environment, mutual hostility based on class. The reality of the period of the October Revolution is considered by Tolgurov in the context of the evolution of individual consciousness. The study of the conceptual layers of the literary text made it possible to trace the transformation of the characters, to determine the spiritual and moral potential of each image, to determine the level of awareness and the degree of involvement of the characters in the historical process. The author's evaluation line contributed to the realization of humanistic concepts and ideas. The work gradually reveals the ideological attitudes of representatives of different social strata, subjective ways of translating the mental component of the people (using the example of the ideological antipodes of the Nuh and the Cossack). All these provisions confirm the scale of the writer's reflection of the specifics of the era, the relevance and artistic and aesthetic value of the novel.